Pengaruh motivasi ekstrinsik, disiplin kerja, dan lingkungan kerja terhadap kinerja pegawai melalui kepuasan kerja pada pegawai direktorat jenderal pajak kanwil DJP Jakarta khusus KPP Badan dan Orang Asing - Efendi, Suryono; Sugiono, Edi; Masdaryanto, Masdaryanto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to analyze and prove the effect of extrinsic motivation, work discipline, work environment, job satisfaction on employee performance, and the effect of extrinsic motivation, work discipline, work environment on job satisfaction, as well as the indirect effect of extrinsic motivation, work discipline, environment. Job satisfaction on employee performance is mediated by job satisfaction. In this study, it is proven that extrinsic motivation, work discipline, work environment, job satisfaction have a positive and significant effect on employee performance, while extrinsic motivation, work discipline, and work environment have a positive and significant effect on job satisfaction. For extrinsic motivation, and work discipline indirectly have a positive and significant effect on employee performance mediated by job satisfaction. While the indirect effect of the work environment on employee performance is mediated by job satisfaction, the results are not significant. The highest job satisfaction mediates work discipline on employee performance, which means that if job satisfaction is increased, work discipline will increase and have an impact on increasing employee performance.